Masters of Public Health: Field Experience and Final Project - Kerns, Michele (My University, 2013)
Service related tinnitus and hearing loss has been a steadily growing cost and concern for veterans and soldiers over the past few decades. The current protocols for education and hearing protection, while an improvement, are not enough to stop the high incidence of hearing loss among military personnel. The purpose of this survey among soldiers at Ft Riley was to determine the sources of compliance issues, as well as the major concerns for wearing hearing protection in the field. The survey results were then compared to the potential for improvement if the concerns were addressed with new technology that has recently become available with active or intelligent hearing protection devices. Results showed that the top concerns were effective communication and the ability to hear important environmental sounds. These concerns correlate with the abilities of the active listening protection and communication systems. Recommendations to improve hearing protection compliance and to reduce hearing loss among soldiers would be to utilize this technology, or similar if available, in training and while soldiers are deployed.
Keywords: Public Health; Fort Riley; Hearing Protection; Public Health (0573)